1995
DOI: 10.1002/ijc.2910600509
|View full text |Cite
|
Sign up to set email alerts
|

Risk of ocular melanoma in relation to cutaneous and IRIS naevi

Abstract: A case-control study was set up to assess the risk of eye melanoma in relation to the number and type of cutaneous melanocytic naevi and pigmented lesions of the iris. Cases comprised 211 unselected ocular melanoma patients attending the Ocular Oncology Clinic at Moorfields Eye Hospital, London, during November 1990 to October 1991 and diagnosed after August 1986. Hospital and general practice controls (416) were recruited in the North East Thames Region of the UK. Cutaneous naevi greater than or equal to 2 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 29 publications
(9 reference statements)
1
21
0
4
Order By: Relevance
“…Our investigation was prompted by the observation that patients with uveal melanomas have a greater number of cutaneous naevi than that of the general population, and that numbers of cutaneous naevi, as well as skin and hair colour, are a function of MC1R genotype (Bataille et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our investigation was prompted by the observation that patients with uveal melanomas have a greater number of cutaneous naevi than that of the general population, and that numbers of cutaneous naevi, as well as skin and hair colour, are a function of MC1R genotype (Bataille et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…While segregation of uveal melanoma and cutaneous melanoma and an association with atypical melanoma have been reported (Bataille et al, 1993;van Hees et al, 1998), most of the uveal melanomas appear to be sporadic (Lynch et al, 1968;Canning and Hungerford, 1988;Singh et al, 1996). Several studies have suggested that atypical naevi, light eye colour and exposure to ultraviolet radiation each represent independent risk factors for uveal melanoma, just as they do for cutaneous melanoma (Rootman and Gallagher, 1984;Dolin and Johnson, 1994;Bataille et al, 1995;Regan et al, 1999). The inference from these data is that genetic susceptibility to uveal melanoma is likely to be mediated through sensitivity to ultraviolet radiation.…”
mentioning
confidence: 99%
“…Conversely, relatives of persons with uveal melanoma often have cutaneous melanomas, especially within the context of the dysplastic nevus syndrome. [15][16][17] The common neural crest origin of uveal and cutaneous melanocytes provides a biological basis for any inherited syndrome, conferring susceptibility to both diseases.…”
mentioning
confidence: 99%
“…This concept is further supported by several case series and case-control studies [ 25 ]. In a prospective study of 207 consecutive patients with ocular melanoma (uveal, conjunctival, and eyelid melanoma), a greater than expected prevalence of cutaneous melanoma and FAM-M syndrome was observed [ 47 ]. Of the ocular melanoma patients, 9 % had the FAM-M syndrome, as compared with 1 % in the control population [ 47 ].…”
Section: Familial Atypical Mole and Melanoma Syndromementioning
confidence: 90%
“…In a prospective study of 207 consecutive patients with ocular melanoma (uveal, conjunctival, and eyelid melanoma), a greater than expected prevalence of cutaneous melanoma and FAM-M syndrome was observed [ 47 ]. Of the ocular melanoma patients, 9 % had the FAM-M syndrome, as compared with 1 % in the control population [ 47 ]. A similar association between uveal melanoma and dysplastic nevi has also been observed by others with an odds ratio ranging from 2.9 to 5.1 [ 48 ].…”
Section: Familial Atypical Mole and Melanoma Syndromementioning
confidence: 93%